STUDI KOMPARATIF USAHATANI BUAH NAGA GOOD AGRICULTURE PRACTICES DAN NON GOOD AGRICULTURE PRACTICES DI DESA JAMBEWANGI, BANYUWANGI - Muhammad Nazil Dwi Ramadhan; Evita Soliha Hani; Anik Suwandari (University of Jember, 2019)
The study was aimed to: (1) The consideration of farmers are applied GAP and Non-GAP in dragon fruit farming. (2) Determine factors which influenced dragon fruit production in GAP and Non-GAP. (3) The cost efficiency between GAP and Non-GAP dragon fruit farming. Descriptive analysis, quadratic function, and independent sample t-test are employed to determine the objective of the research. The study showed that: (1) There were some considerations in applying the GAP of dragon fruit farming such the higher selling price to collectors, the affordable manure and fungicide costs, and eco-friendly. Meanwhile, the consideration of farmers in applying Non-GAP of dragon fruit farming was the larger size of fruit, the higher excitement of the consumers, and it was easier to obtain fungicide and manure. (2) In GAP farming number of plants, organic manure and labor force were significantly influenced toward dragon fruit’s production. While cropland acreage and fungicide had no a significant effect. In the other side, dragon fruit’s production in Non-GAP farming was significantly influenced by number of plants, organic manure, and labor force. While cropland acreage, plant lifetime, anorganic manure, fungicide, and growth hormone substances had no a significant effect. (3) The independent sample t-test analysis showed the significant value (sig. 2-tailed) had 0,000 < α (0,05), it means that there were significant differences in cost efficiency between GAP and Non-GAP.